Hesperidin Suppresses the Proliferation of Prostate Cancer Cells by Inducing Oxidative Stress and Disrupting Ca2+ Homeostasis - Seon Ae Jeong; Changwon Yang; Jisoo Song; Gwonhwa Song; Wooyoung Jeong; Whasun Lim (MDPI AG, 2022)
Although androgen deprivation therapy is mainly used for its treatment, the mortality rate of prostate cancer remains high due to drug resistance. Hence, there is a need to discover new compounds that exhibit therapeutic effects against prostate cancer with minimum side effects. Hesperidin is a flavonoid carbohydrate isolated from citrus fruits. It has antiproliferative effects in various cancer types; however, whether it can modulate cell proliferation by modulating the key targets of cancer therapy, including intracellular signaling pathways and oxidative stress, remains unknown. Therefore, we confirmed that hesperidin suppressed the proliferation of prostate cancer cells, PC3 and DU145. Hesperidin induced cell death by regulating the cell cycle and inhibited the expression of proliferating cell nuclear antigen, a cell proliferation marker. Hesperidin also promoted the generation of reactive oxygen species and induced mitochondrial membrane depolarization and endoplasmic reticulum stress in prostate cancer cells. Moreover, as hesperidin increased Ca2+ levels in prostate cancer cells, we co-treated the inositol 1,4,5-trisphosphate receptor inhibitor, 2-aminoethyl diphenyl borate (2-APB), with hesperidin. Notably, 2-APB restored cell proliferation, which was reduced to control levels by hesperidin. In addition, hesperidin inhibited the activation of the phosphoinositide 3-kinase and mitogen-activated protein kinase signaling pathways. Hesperidin also enhanced the anticancer effects of the chemotherapeutic agent, cisplatin, in both PC3 and DU145 cells. Taken together, these results suggest that hesperidin can be used as a potential therapeutic adjuvant in prostate cancer as it can inhibit cell proliferation by mediating oxidative stress and increasing Ca2+ levels.